The global, regional, and national burden of type 2 diabetes mellitus attributable to low physical activity from 1990 to 2021: a systematic analysis of the global burden of disease study 2021 - Jiehua Wei; Luying Fan; Zixuan He; Senmao Zhang; Ying Zhang; Xidi Zhu; Fan Xia; Xinli Song; Lizhang Chen; Zhiyong Zou; Tingting Wang (International Journal of Behavioral Nutrition and Physical Activity)
Abstract Background Low physical activity (LPA) is a leading risk factor for type 2 diabetes mellitus (T2DM). We examine the temporal and spatial trends in the burden of T2DM attributable to LPA at the global, regional, and country scales. Methods Data were obtained from the Global Burden of Disease Study 2021. The numbers of deaths and disability-adjusted life years (DALYs) of LPA-related T2DM, and the corresponding age-standardized mortality rate (ASMR) and age-standardized DALYs rate (ASDR) were compared across regions and countries by age, sex, and sociodemographic index (SDI). The annual percentage changes (EAPCs) in the ASMR or ASDR were calculated to quantify temporal trends from 1990 to 2021. We also quantified the relationship between SDI and the ASMR and ASDR of T2DM attributable to LPA. Results Globally, the number of T2DM deaths and DALYs attributable to LPA were approximately 0.15 million and 5.52 million respectively in 2021, which more than doubled compared to 1990. Over the past 32 years, the global EAPCs of ASMR and ASDR were 0.26 (95% CI: 0.20, 0.31) and 0.97 (95% CI: 0.93, 1.02), respectively. The ASMR or ASDR had a reverse U-shaped relationship with the SDI, with the most severe burden observed in the low-middle and middle SDI regions. The age group older than 60 years had the highest rate of DALYs for LPA-related T2DM in 2021, while the 25–44 age group showed the largest increase between 1990 and 2021. Conclusions Over the past 32 years, the global burden of LPA-related T2DM has continued to increase at an alarming rate in almost all countries, particularly in regions with low-middle and middle SDI. Substantial increases in national action are urgently needed to target elder populations especially in low-middle and middle SDI regions, and special efforts should be made to promote physical activity in young adults with LPA.